Finite element study of mode I crack opening effects in compression-loaded cracked cylinders. (15th April 2017) - Berer, M.; Mitev, I.; Pinter, G.
Graphical abstract: Highlights: Mechanism of mode I crack opening in compression-loaded cylinders. Crack orientation in cylinders which was not studied before in the literature. Contour integral to determine stress intensity factor K for different crack lengths. One-dimensional load-normalized K-curves (Knorm  = function(crack length)). 2-dimensional load-normalized K-curves as a result of cylinder scaling. Crack closing effects in the vicinity of the Hertzian contact zone. Abstract: Mode I crack opening effects in compression-loaded cracked cylinders were examined using finite element analysis. The situation ahead of the crack tip was characterized using linear elastic fracture mechanics in the form of the stress intensity factor (K) concept. Different cylinder dimensions in combination with different loads and crack radii (circular crack shapes were used) were investigated. By using the line load as normalization parameter for the K values, load independent K-curves (K as a function of the normalized crack length a/W) were obtained. The K-curves were compared for different cylinder dimensions to examine the scaling behavior.